Diversity in the Early Phases of Product Development - Ehrenmann, Steffen; Warschat, Joachim (International Journal of Industrial Engineering and Management, 2013)
Internationalization of R&D activities and the strategy of reverse innovation are new challenges of product developmentwhich will be discussed in this paper. These challenges in companies‘ environment require organizational skills to reduce uncertainties as well as to enable flexibility and adaptability.The consideration and use of diversity in the early phases of product development can be a way to meet these challenges. Therefore potential benefits of diversity and the relationship between diversity and innovation are shown in this paper. The potential opportunities of diversity but also its challenges like conflicts as well as communication and cooperation barriers point to the need for a management model which systematically considers and handles diversity in the early phases of product development. Article history: Received (4 May 2012); Revised (17 November 2012); Accepted (16 January 2013)